Elemental analysis in environmental land samples by stand-off laser-induced breakdown spectroscopy - Fang, Xiao; Ahmad, Sheikh R. (Elsevier, 2013)
The stand-off detection and analysis of environmental land samples have been demonstrated using laser-induced breakdown spectrometry. The samples of interest have included soils and vegetation powder. Elements Hg, As, Pb, Zn, Cd and Cr have been spectrally analysed with a focus on Hg as a trace contaminant in the samples. It is found that element Fe, usually contained in land samples, is a main source of spectral interference for Hg detection due to its ever present iron emission line at 253.68 nm that is closely adjacent to the strongest Hg emission line at 253.65 nm, and hence, a high resolution of spectral detection is necessary. The strong spectral signals from Bremsstrahlung emission in laser-induced plasma and atomic emission of Fe of high concentration caused a significant reduction in detection resolution in the use of image intensifier of an ICCD. The limit of detection at ~8 ppm for Hg detection in soil samples with iron as a minor constituent has been achieved, using an optical chopper and a CCD detector for laser-induced breakdown spectroscopy (LIBS) signal detection. Such detection method in LIBS system has shown a great advantage in determining trace elements from interfering elemental constituents in land sample matrixes.
Keywords: Emission Line; Spectral Signal; Image Intensifier; Spectral Interference; Tomato Leave